Multi-element (13C, 2H and 34S) bulk and compound-specific stable isotope analysis for authentication of Allium species essential oils. (August 2021) - Cuchet, Aurélien; Anchisi, Anthony; Telouk, Philippe; Yao, Yijiao; Schiets, Frédéric; Fourel, François; Clément, Yohann; Lantéri, Pierre; Carénini, Elise; Jame, Patrick; Casabianca, Hervé
Abstract: Pure and natural essential oils of Allium species are primarily used in the food industry, but due to their low yield, production quantities can be difficult to achieve and thus can be highly expensive. Due to these problems, adulterations are a reality in this field. The purpose of this research is to develop a multi element stable isotope analysis methodology for authentication of the essential oils of leek, onion, shallot, and chive. Naturalness of these essential oils was achieved by assessment of compound specific δ 13 C and δ 34 S: an addition of 5% of synthetic compound can be detected. Chemometric models were undertaken to assess purity by distinction of the Allium samples according to their species origin using bulk stable and compound specific δ 13 C, δ 2 H, δ 34 S, and compositions of their major metabolites dipropyl disulfide, dipropyl trisulfide, methyl propyl disulfide, and methyl propyl trisulfide. Highlights: Assessment of δ 34 S compound specific isotope analysis (CSIA) using GC/MC-ICP-MS. δ 13 CCSIA and δ 34 SCSIA determination for authentication of naturalness. Addition of 5% of synthetic sulphur-containing compound can be highlighted. Chemometric models for species differentiation.